ANTIOXIDANT PROPERTIES OF ROMANIAN GRAPE VARIETIES - MIHAELA MULȚESCU; IULIA-ELENA SUSMAN (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
This study explores the application of the photochemiluminescence assay in two distinct extracts, hydrophilic and lipophilic, alongside the DPPH method to evaluate the antioxidant potential of three grape varietis (Chasselas, Romanian Muscat, and Muscat Hamburg). The results revealed significant phenolic compound concentrations, ranging from 21.68 to 43.44 mg gallic acid equivalent per 100 g of fresh weight. Flavonoid content was between 4.26 and 8.86 mg rutin equivalent per 100 g of fresh weight, while anthocyanin content varied from 0.16 to 7.02 mg cyanidin-3-glucoside equivalent per 100 g of fresh weight. Among the tested grapes, Muscat Hamburg demonstrated the highest antioxidant activity using DPPH method. In terms of antioxidant capacity, Chasselas exhibited the highest value in the hydrophilic system, while Muscat Hamburg showed the greatest antioxidant capacity in the lipophilic system.